And i will try to fix you: A study of heterogeneity in job satisfaction with implications for flexible employment contracts - Aekapol Chongvilaivan; Nattavudh Powdthavee (Institute for the Study of Labor (IZA), 2011)
This paper is an empirical study of slope heterogeneity in job satisfaction. It provides evidence from the generalized ordered probit models that different job characteristics tend to have different distributional impacts on the overall job satisfaction. For instance, standard models tend to significantly underestimate the effects of monthly salary and hours worked at generating the highly satisfied workers, whilst lowering the incidence of the very dissatisfied workers. Although our results should be viewed as illustrative, we provide discussions of their potential implications for employers and they could help with the design of employment contracts.
urn:nbn:de:101:1-201108092956
Keywords: J53; D61; 330; job satisfaction; heterogeneity; employment contract; generalized ordered probit; salary; work-life balance